التوارث بين الزوجين على ضوء قانون الأسرة الجزائري - علالي, ثريا; محروق, كريمة (University of Eloued جامعة الوادي, 2021)
يعتبر حق التوارث بين الزوجين من أهم الحقوق المالية المستحقة بين الطرفين عند وفاة أحدهما, ومن خلال هذا الموضوع سيتم تسليط الضوء على الأحكام العامة التي تستلزم استحقاق الإرث بين الزوجين بالتركيز على الرابطة الزوجية التي تعد سببا موجبا للإرث بينهما إذ وبمجرد انعقاد عقد الزواج يثبت التوارث ولا يتوقف إطلاقا على الدخول، لأن العبرة بالعقد الصحيح المستوفي لركنه وشروطه المحددة في نص المادتين 9و9مكرر من ق أج, كما نتعرض إلى الحالات التي يتم فيها التوارث بين الزوجين وكذا إبراز أهم الإشكالات التي تطرح في هذا الصدد. Upon the death of one of them,the right of inheritance between spouses is one of the most important financial rights.This research will shed the light on the general provisions that are required for the entitlement of inheritance between spouses with a specific focus on the marital bond, which is the ultimate reason for the inheritance. Once a correctmarriage contract is signed inaccordancewith the Algerian law of the criminal procedures, specifically article number 9, the inheritance is proven. The study also examines the cases in which inheritance between spouses happen,and its most significant resulting problems.
مجلد12، عدد1
Keywords: التوارث بين الزوجين ; العقد الصحيح ; الموت التقديري ; الحياة الحقيقية ; موانع الإرث ; أصحاب الفروض ; موت المورث; Marital; Inheritance between spouses;the right ;contract;discretionary death; real life; inheritance contraindications; legal heirs; death of the testator